(untitled) (London Journal of Medical and Health Research, 2026)
Airway closure, first recognized by Laennec and later quantified in studies by Dollfuss, Hedenstierna and Hughes, represents a physiological phenomenon with far-reaching clinical consequences. While often overlooked in critical care, its role in promoting atelectasis, impaired gas exchange, and ventilator-induced lung injury is well established. The present narrative review revisits the fundamental physiology of airway closure, its exacerbation in anaesthesia and obesity, and its near-universality in mechanically ventilated ARDS patients. A reinterpretation of pleural pressure data from landmark studies, suggests that airway closure may be far more prevalent than currently appreciated. Strategies such as optimal PEEP and avoidance of high oxygen fractions are discussed, with emphasis on the urgent need for better integration of airway closure physiology into clinical practice. This article re-examines how positive airway pressure in combination with elevated intrathoracic pressure — the inevitable companion of positive pressure ventilation — underlies many of the adverse effects attributed to modern mechanical ventilation. By contrast, negative pressure ventilation, long abandoned, may offer physiological advantages worth reconsidering. The question we must now ask is: could a return to negative extra-thoracic pressure — or a hybrid model — prevent the very complications we have come to accept as inevitable?